2020
DOI: 10.22270/jddt.v10i5.4344
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical, Histological, Serological and Therapeutic Study of Children Celiac Disease in Western Algeria Region

Abstract: Objectives: To determine the epidemiological, clinical, histological, serological and therapeutic profile of celiac disease in children in Western Algeria region.Methods: 250 patients over a period of three years (2016 - 2019) from the pediatric department of the University Hospital of Oran (West Algeria) were included in our retrospective study.Results: We noticed a female predominance with a sex ratio F/M = 1.57. Symptoms were defined by typical (73.2%) and atypical (26.8%) forms, digestive disorders (47.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The serological tests were necessary for the diagnosis of the disease, although the current study's results showed that serology was positive in 85.2% of celiac patients. The present study's results are similar to the results of other studies (21,24), recalling that even in infants (90.0%), children (80.7%), and (89.2%) adults, the tests mainly (IgA and IgG a-tTG, IgA endomysial antibodies, and IgA antigliadin antibodies) were significantly higher for children than adults, which underlines an excellent predictive value to confirm the diagnosis (25,26). A The histological test defined by a duodenal biopsy remains an examination of reference to confirm the diagnosis of celiac disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The serological tests were necessary for the diagnosis of the disease, although the current study's results showed that serology was positive in 85.2% of celiac patients. The present study's results are similar to the results of other studies (21,24), recalling that even in infants (90.0%), children (80.7%), and (89.2%) adults, the tests mainly (IgA and IgG a-tTG, IgA endomysial antibodies, and IgA antigliadin antibodies) were significantly higher for children than adults, which underlines an excellent predictive value to confirm the diagnosis (25,26). A The histological test defined by a duodenal biopsy remains an examination of reference to confirm the diagnosis of celiac disease.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the total grade (Marsh ≥ 3) was present in adults more frequently than in children. The aforementioned results were also reported by other studies (21,27).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation